ESTRUS AND OVULATION INDUCTION OF POSTPARTUM LACTATING ONGOLE COWS WITH STEROIDS, GONADOTROPINS AND PROSTAGLANDIN - NAIDU, G VENKATA; RAO, A SESHAGIRI; NAIDU, K VENUGOPAL; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
In the present study with a view to obviate prolonged calving interval, four estrus and ovulation induction hormonal protocols were initiated on day 45 postpartum with 20 postpartum lactating cows in each group. The cows in the treatment group ’P: (CIDf:t PGF 211 +EB) exhibited 100 per cent response and ovulation with a better degree synchrony. The estrus duration was found to be significantly (P< 0.05) longer in treatment A and B (20.60 and 18.40 hours) than C, D and E (control) (15.24, 14.66 and 15.54) groups. The reproductive performance of A, B, C treatments were found to be superior over O and E (control) group. The mean interval from calving to fertile estrus (68.11, 73.44, 71.80, 76. 71 vs 113.52 days) and the Al index (1.63, 1.84, 1.70, 1.83 vs 2.42) of the treatment groups was superior over control group. Shortened service period by 45.41, 40.08, 41.72 and 36.81 days with treatment A, B, C and D treatments over control group. It is concluded that treatment of PP lactating Ongole cows with hormonal agents including progesterone. EB, GnRH and PGF 24 reduced the service period and improved the reproductive performance.